Globalization in practice - Thrift, Nigel J.; Tickell, Adam; Woolgar, Steve; Rupp, William H. (Oxford University Press, 2014)
The concept of globalization has become ubiquitous in social science and in the public consciousness and is often invoked as an explanation for a diverse range of changes to economies, societies, politics and cultures - both as a positive liberating force and as a wholly negative one.